Special Speed Endurance Effect of 800m Running on Some Physiological Indictors and Achievement of Physically Disabled Men Class (T47 - T46) - Husain Abdul-Hadi Ubaida; Ahmed Mohamed Ismail (College of Physical Education and Sport Sciences, 2021)
The research aimed at identifying the effect of special speed endurance training on some physiological indicators in 800m runners with physical disabilities. The researchers used the experimental method on (4) physically disabled 800m runners. They concluded significant differences in the subjects under study as well as significant differences in some physiological indicators during rest and after physical effort. The results show development in the level of some physiological indicators during rest and after effort. The researchers recommended using these training programs in individual sports as well as team sports for physically disabled athletes.